2015
DOI: 10.1007/s11886-015-0580-1
|View full text |Cite
|
Sign up to set email alerts
|

Interventional CMR: Clinical Applications and Future Directions

Abstract: Interventional cardiovascular magnetic resonance (iCMR) promises to enable radiation-free catheterization procedures and to enhance contemporary image guidance for structural heart and electrophysiological interventions. However, clinical translation of exciting pre-clinical interventions has been limited by availability of devices that are safe to use in the magnetic resonance (MR) environment. We discuss challenges and solutions for clinical translation, including MR-conditional and MR-safe device design, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 87 publications
0
41
0
Order By: Relevance
“…Magnetic resonance (MR) imaging offers an alternative technique for device monitoring during minimally invasive delivery and follow-up procedures. [14] Herein we present the development of a shape memory polymer (SMP) porous scaffold that can be visualized via MR-imaging, as well as possible imaging via X-ray fluoroscopy for dual imaging modality procedures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Magnetic resonance (MR) imaging offers an alternative technique for device monitoring during minimally invasive delivery and follow-up procedures. [14] Herein we present the development of a shape memory polymer (SMP) porous scaffold that can be visualized via MR-imaging, as well as possible imaging via X-ray fluoroscopy for dual imaging modality procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The use of MR imaging as an alternative for pediatric applications provides a safer method of visualizing both the procedure and post-operative images for both the patient and the technicians. [14]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI-guided excision and ablation of head 12 , spine 13 , abdominal 14 and pelvic 15 tumors is performed at hundreds of sites world-wide. Intra-operative MRI guidance during cardiac electro-physiological (EP) mapping and thermal ablative procedures has been under development in animal models for the past 15 years 1618 . These animal EP procedures have shown that MRI methods can detect the causes for arrhythmia recurrence post-procedure and can also determine the exact amount of tissue that has been ablated.…”
mentioning
confidence: 99%